Electrochemical characterization of Fe center from hemin binding with Yersinia pestis heme-protein acquisition system. (1st March 2019) - Zhao, Yaqin; Cui, Xiaofang; yang, Jing; Yu, Lu; Yang, Binsheng
Abstract: The interaction of Yersinia pestis (YpHmuT) with Fe center on hemin (ferric form) or heme (ferrous form) was investigated by differential pulse voltammetry (DPV), cyclic voltammetry (CV), square wave voltammograms (SWV), electrochemical impedance spectroscopy (EIS) and spectra. Electrochemical signals of hemin/heme were strongly influenced by virtue of interacting with YpHmuT. The 2:1 stoichiometric ratio of the hemin or heme to YpHmuT was confirmed. YpHmuT binds to ferric hemin with pentacoordinate and high-spin and binds to ferrous heme with low-spin. Our findings may provide useful data for understanding biological processes of hemin transportation in Yersinia pestis . Graphical abstract: Square wave voltammograms of hemin2 -YpHmuT (a) and heme2 -YpHmuT (b). Hemin2 -YpHmuT: green: YpHmuT backbone (PDB:3NU1 ), red: hemin a, blue: hemin b; Heme2 -YpHmuT: green: YpHmuT backbone (PDB:3NU1 ), orange: heme a, pink: heme b.